Analisa Jabatan dan Manajemen Kompetensi Sebagai Upaya Meningkatkan Kinerja Karyawan: Studi Kasus Pada PT. Uno - Lorenzy Oshel (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2022)
Human resources have significant roles in the company in order to achieve success. Human resource management is very essential to improve the performance of an organization or a company. There are many ways to manage human resources, one of them is through performing a job analysis. This research aims to analyze the job position in one of the property companies called PT. Uno. The job analysis will result in the job description and job-specific competency. The summary of the job description will be used to identify the specific competency for each job specification. The compilation of the job description and the specific competency will be conducted on two managerial positions. The compilation of the job description showing results that the planning supervisor job position has three main responsibilities and three competency specifications. While quantity surveyor supervisor job position has four main responsibilities and three competency specifications.